Customer experience and commitment on eWOM and revisit intention: A case of Taladtongchom Thailand - Wanwisa Paisri; Chutima Ruanguttamanun; Narissara Sujchaphong (Cogent Business & Management, 2022)
This study examines the effects of customer experience on electronic word of mouth (eWOM) and revisit intention and investigates whether commitment mediates the relationship between customer experience, eWOM, and revisit intention in the tourism context. A survey method by using a self-administered questionnaire with a quantitative approach was conducted. Quota sampling was adopted, the data were collected in 12 markets, for a total of 52 questionnaires per market. The total sample sizes are 624 tourists. Structural equation modeling (SEM) is used for data analysis. The results indicate that customer experience has a significant and positive relationship with affective and continuance commitment. Affective commitment mediates the relationship between entertainment and escapist experience and eWOM and revisit intention. The study's findings the extended role of customer experience and the types of commitment provide meaningful theoretical implications. Hence, managers should focus on customer experience to generate customers' commitment, positive eWOM, and revisit intention.
Keywords: 650; affective commitment; continuance commitment; customer experience; electronic word of mouth (eWOM); revisit intention; Thailand; tourism